2010
DOI: 10.1111/j.1462-5822.2010.01504.x
|View full text |Cite
|
Sign up to set email alerts
|

Pasteurella multocida Toxin-induced Pim-1 expression disrupts suppressor of cytokine signalling (SOCS)-1 activity

Abstract: SummaryPasteurella multocida Toxin (PMT) is a mitogenic protein toxin that manipulates signal transduction cascades of mammalian host cells and upregulates Janus kinase (JAK) and signal transducers of transcription (STAT) activity. Here we show that in the presence of PMT, increased levels of suppressors of cytokine signalling-1 (SOCS-1) proteins significantly enhance STAT activity. This occurs via PMT-induced expression of the serine/ threonine kinase Pim-1 and subsequent threonine phosphorylation of SOCS-1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Recent studies have revealed that in addition to the ␣ subunit of the heterotrimeric G q protein (488)(489)(490), PMT also acts on other G proteins, i.e., G 11 , G i , and G 12/13 (488)(489)(490)(491)(492)(493)(494). A number of studies have implicated PMT as a modulator of host immunity (475,(495)(496)(497)(498) and cellular differentiation and proliferation (476,477,485,(499)(500)(501)(502)(503)(504)(505)(506)(507). Interestingly, because of its potent mitogenic and proliferative properties, there has been speculation that exposure to PMT might play a role in cancer predisposition as a longterm consequence of infection with toxinogenic P. multocida (485,495,499,504,505,(508)(509)(510).…”
Section: Survival In the Host Environmentmentioning
confidence: 99%
“…Recent studies have revealed that in addition to the ␣ subunit of the heterotrimeric G q protein (488)(489)(490), PMT also acts on other G proteins, i.e., G 11 , G i , and G 12/13 (488)(489)(490)(491)(492)(493)(494). A number of studies have implicated PMT as a modulator of host immunity (475,(495)(496)(497)(498) and cellular differentiation and proliferation (476,477,485,(499)(500)(501)(502)(503)(504)(505)(506)(507). Interestingly, because of its potent mitogenic and proliferative properties, there has been speculation that exposure to PMT might play a role in cancer predisposition as a longterm consequence of infection with toxinogenic P. multocida (485,495,499,504,505,(508)(509)(510).…”
Section: Survival In the Host Environmentmentioning
confidence: 99%
“…Since Tlr8 −/− mice had a hyperactive IFN response and reduced Socs-1 , we hypothesized that TLR8 signaling may regulate Socs-1 expression. It has been reported that TLR7/8 signaling induces the expression of Socs-1 in HEK293 cells, yet these studies did not rule out if this signaling is dependent on TLR7 or TLR8 alone, or an effect of combined TLR7 and TLR8 ligation (91). In our report, we demonstrated that SOCS-1 partnered with TLR8, but not TLR7, suggesting SOCS-1 utilizes TLR8 as an adaptor molecule for its regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The PMT-dependent stimulation of Akt was attributed to the PMT-mediated release of Gβγ and subsequent Gβγ activation of PI3K [123]. On the other hand, signal transducer and activator of transcription (STAT) signaling pathways are known to regulate expression of Pim kinases [189], and it was shown that PMT stimulates the prolonged activation of JAK2/STAT3/5 pathways in a Gα q -dependent manner [190,191].…”
Section: Pmt and Apoptosismentioning
confidence: 98%